The influence of charge geometry on the response of cylinders to internal air blasting - Davids, Sean (Blast Impact and Survivability Research Unit, 2016)
The effect of charge geometry on the structural response of right circular cylinders, subjected to internal blast loading, was investigated. Thin-walled, seamless 304 stainless steel cylinders were subjected to blast loads from partially confined bare cylindrical PE4 charges with different diameter and aspect ratios(charges length to charge diameter). The diameters of interest were: 25 mm (aspect ratios of 0.5 -3). 30 mm (aspect ratios of 0.5 -1.6). 35 mm (aspect ratios of 0.5 - 1.1). 40 mm (aspect ratios of 0.5 - 0.9). The effect of aspect ratio, for the constant diameter or constant mass cases, on the structural response of the cylinders (that is, diametric deflection, axial impulse, and axial shortening) is reported. Cylindrical charges with an aspect ratio of 1, were compared to spherical charges of equivalent mass. For charges with constant diameter with varying length: The diametric deflection increased with increasing aspect ratio. The axial shortening increased with increasing aspect ratio. The axial impulse increased with increasing aspect ratio. For charges with constant mass with varying diameter and length: The long charges (that is, charges with aspect ratios greater than 1) caused larger diametric deflections than their mass equivalent short (that is, charges with aspect ratios less than 1) charges. This is because the long charges had more side effective charge mass (that is, the mass of the charge that contributes directly to the diametric deflection of a cylinder) than the shorter charges. The short charges transferred more axial impulse to the ballistic pendulum, because they had more axial effective charge mass (that is, the mass of the charge that contributes directly to the axial impulse that is transferred to a ballistic pendulum) than their mass equivalent long charges. It was observed that a lighter charge can diametrically deflect a cylinder more effectively than a heavier charge, if its side effective charge mass is greater than that of the heavier charge. The structural responses of the cylinders obtained from cylindrical charge detonations were greater than those obtained from the mass equivalent spherical charge detonations. The deflections resulting from the cylindrical charges were also more localised compared to the spherical charges.